Altered Gut Microbiota Composition Is Associated With Back Pain in Overweight and Obese Individuals - Dekker Nitert, Marloes; Mousa, Aya; Barrett, Helen L.; Naderpoor, Negar; De Courten, Barbora (Frontiers in Endocrinology, 2020)
Background: Back pain is the leading cause of disability worldwide and is associated with obesity and chronic low-grade inflammation. Alterations in intestinal microbiota may contribute to the pathogenesis of back pain through metabolites affecting immune and inflammatory responses. Aims and Methods: We compared the gut microbiota composition in a cohort of 36 overweight or obese individuals with or without self-reported back pain in the preceding month. Participants were characterized for anthropometry; bone health; metabolic health; inflammation; dietary intake and physical activity. Results: Demographic, clinical, biochemical characteristics, diet and physical activity were similar between participants with (n=14) or without (n=22) back pain. Individuals with back pain had a higher abundance of the genera Adlercreutzia (p=0.0008; FDR=0.027), Roseburia (p=0.0098; FDR=0.17), and Uncl. Christensenellaceae (p=0.02; FDR=0.27) than those without back pain. Adlercreutzia abundance remained higher in individuals with back pain in the past 2 weeks, 6 months, and 1 year. Adlercreutzia was positively correlated with BMI (rho=0.35, p=0.03), serum adipsin (rho=0.33, p=0.047), and serum leptin (rho=0.38, p=0.02). Conclusions: Our findings suggest that back pain is associated with altered gut microbiota composition, possibly through increased inflammation. Further studies delineating the underlying mechanisms may identify strategies for lowering Adlercreutzia abundance to treat back pain.